Hepatocellular Glycogen Accumulation in the Setting of Poorly Controlled Type 1 Diabetes Mellitus: Case Report and Review of the Literature - Atinuke Aluko; Ikponmwosa Enofe; Jacob Burch; Julie Yam; Nazia Khan (Case Reports in Hepatology)
Glycogenic hepatopathy (GH) is the accumulation of glycogen in the hepatocytes and represents a rare complication in patients with diabetes mellitus (DM), most commonly type 1 DM. We present a case of a 23-year-old woman with a medical history of poorly controlled type 1 DM and gastroesophageal reflux disease (GERD) who presented with progressively worsening right-sided abdominal pain. Diagnostic workup resulted in a liver biopsy with hepatocytes that stained heavily for glycogen with no evidence of fibrosis or steatohepatitis. A diagnosis of glycogenic hepatopathy was made, and an aggressive glucose control regimen was implemented leading to resolution of symptoms and improvement in AST, ALT, and ALP. In addition to presenting this rare case, we offer a review of literature and draw important distinctions between glycogenic hepatopathy and other differential diagnoses with the aim of assisting providers in the diagnostic workup and treatment of glycogenic hepatopathy.